Capillary Imbibition of Concrete Containing Cold Bonded Fly Ash-Based Lightweight Aggregate in a Salt Environment - Risdanareni, Puput; Sulton, Mohammad; Nindyawati, Nindyawati; Rosyidi, Ditya Hafidz; Ekaputri, Januarti Jaya; Razak, Rafiza Binti Abd.; Abdullah, Mohd Mustafa Al Bakri (Civil Engineering Dimension, 2026)
Cold bonded lightweight aggregate generated from fly ash (FA LWA) has become an interesting approach to increase the consumption of fly ash and prevent over-mining of natural aggregate. However, using the cold-bonded hardening method could increase the number of open pores in LWA, making the concrete containing this LWA face an increased risk of degradation due to water ingress. Thus, in this research, the effect of using FA LWA in concrete on the mechanical and transport properties in a salt environment is being investigated. Three aggregate replacement ratios of 0, 50, and 100% were applied, while the salt environment was mimicked with NaCl and Na2SO4 solutions. The results show that the optimum replacement rate of FA LWA was 50%. Regarding the transport properties, exposing concrete to a salt environment (NaCl or Na2SO4) proved to slow down the capillary imbibition rate slightly.